Prospects of doubling global wheat yields. (12th March 2013) - Hawkesford, Malcolm J.; Araus, Jose‐Luis; Park, Robert; Calderini, Daniel; Miralles, Daniel; Shen, Tianmin; Zhang, Jianping; Parry, Martin A. J.
Abstract While an adequate supply of food can be achieved at present for the current global population, sustaining this into the future will be difficult in the face of a steadily increasing population, increased wealth and a diminishing availability of fertile land and water for agriculture. This problem will be compounded by the new uses of agricultural products, for example, as biofuels. Wheat alone provides ≥20% of the calories and the protein for the world's population, and the value and need to increase the production is recognized widely. Currently, the world average wheat yield is around 3 t/ha but there is considerable variation between countries, with region‐specific factors limiting yield, each requiring individual solutions. Delivering increased yields in any situation is a complex challenge that is unlikely to be solved by single approaches and a multidisciplinary integrated approach to crop improvement is required. There are three specific major challenges: increasing yield potential, protecting yield potential, and increasing resource use efficiency to ensure sustainability. Since the green revolution, yields at the farm gate have stagnated in many countries, or are increasing at less than half the rate required to meet the projected demand. In some countries, large gains can still be achieved by improvements in agronomy, but in many others the yield gains will only be achieved by further genetic improvement. In this overview, the problems and potential solutions for increased wheat yields are discussed, in the context of specific geographic regions, with a particular emphasis on China. The importance and the prospects for improvement of individual traits are presented. It is concluded that there are opportunities for yield increase but a major challenge will be avoiding a simultaneous increase in resource requirements.